Kelayakan lokasi budidaya ikan Kuwe (Caranx sp.) ditinjau dari parameter fisika kimia kualitas air pada karamba jaring apung di Desa Tuntung Timur Kabupaten Bolaang Mongondow Utara - Datunsolang, Frayogi; Kusen, Diane; Kalesaran, Ockstan J.; Undap, Suzanne L.; Sambali, Hariyani; Wantasen, Adnan S.; Salindeho, Indra (Universitas Sam Ratulangi, 2021)
This study aimed: (1) to analyze the physical and chemical parameters of water quality of the giant travelly fish (Caranx sp) culture area in floating net cages (KJA) in Tuntung Timur Village, Bolaang Mongondow Utara Regency, and (2) to analyze the feasibility of water quality of the giant travelly fish (Caranx sp) in east Tuntung Village, North Bolaang Mongondow Regency. The Â physical and chemical parameters of water at the cultivation site of Caranx sp in floating net cages were measured in situ, including temperature, salinity, brightness, dissolved oxygen and pH. Chemical physics parameters in floating net cages, namely: temperature ranges from 28.6 oC - 33.3 oC, salinity 30 - 33 0/oo, pH 7.6 - 7.9, oxygen content 3, 9 - 4.3 mg / l and water transparency of 7.4 m - 9.9 m. The giant travelly fish aquaculture in KJA in east Tuntung village is an enlargement activity, the seeds were stocked from bagan and the surrounding waters, the size of the seeds ranged from 8-12 cm, and the stocking density was 500-600 fish. Maintenance was carried out for 5-6 months and harvested at sizes 300-4000 gr/individu. The water quality surrounding KJA was ideal for fish farming activities.